The Disposition of Our Public Lands - Hart, Albert Bushnell (Quarterly Journal of Economics, 1887)
Journal Article The Disposition of Our Public Lands Get access Albert Bushnell Hart Albert Bushnell Hart Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 169–183, https://doi.org/10.2307/1880769 Published: 01 January 1887